Exploring the efficacy of recombinant human pro-urokinase in catheter-directed thrombolysis for acute lower extremity deep venous thrombosis patients - Tao Ma; Cangtuo Li; Guang Song; Shaoxin Yao (BMC Cardiovascular Disorders)
Abstract Background Effective and innovative treatment for patients with acute lower-extremity deep venous thrombosis (DVT) is lacking. This study explored the use of recombinant human pro-urokinase (rhPro-UK) in catheter-directed thrombolysis for acute DVT patients. Methods A retrospective analysis included 85 acute DVT patients undergoing CDT from January 2021 to December 2023. Patients were divided into an observation group (n = 43, rhPro-UK) and a control group (n = 42, UK). Outcomes assessed included total effective rate, venous patency score, limb circumference differences, coagulation parameters (PT, APTT, Fg), adverse events (BARC criteria), and post-thrombotic syndrome (PTS) incidence at 6 months (Villalta scale). Results The observation group treated with rhPro-UK demonstrated superior clinical outcomes compared to the control group receiving urokinase. The total effective rate was significantly higher in the rhPro-UK group (P = 0.011), with improved venous patency reflected by a lower post-treatment patency score (P = 0.009) and higher patency rate (80.86% vs. 72.86%, P = 0.045). Limb swelling reduction was more pronounced in the rhPro-UK group, evidenced by smaller thigh (P = 0.002) and calf circumference differences (P = 0.001). Coagulation function improved significantly, with prolonged PT (P = 0.002) and APTT (P = 0.001), alongside reduced fibrinogen levels (P < 0.001). Safety outcomes favored rhPro-UK, with fewer total bleeding events (14.29% vs. 4.65%, P = 0.039) and no major bleeding (BARC Type 3) observed. At 6-month follow-up, the rhPro-UK group exhibited a markedly lower incidence of post-thrombotic syndrome (9.3% vs. 26.2%, P = 0.034) and sustained venous patency, confirming its long-term efficacy. Conclusion CDT with rhPro-UK significantly improves venous patency, reduces limb swelling, optimizes coagulation function, and minimizes complications compared to UK. Its fibrin-targeted mechanism enhances clinical efficacy and safety, supporting its adoption as a superior thrombolytic for acute DVT. Trial registration Not applicable.